2017
DOI: 10.1007/s10103-017-2224-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser treatment stimulates hair growth via upregulating Wnt10b and β-catenin expression in C3H/HeJ mice

Abstract: This study was conducted in order to evaluate the role of low-level laser treatment (LLLT) in hair growth in C3H/HeJ mice. Healthy C57BL/6 mice were randomly divided into two groups: with and without low-level laser treatment. The skin color of each mouse was observed each day. Skin samples were collected for H&E, immunofluorescence, PCR, and western blot analysis, to observe the morphology of hair follicles and detect the expression levels of Wnt10b and β-catenin. Observation of skin color demonstrated that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Comprehensive single-cell gene expression analysis revealed that Ccr2 gene expression was elevated in recruited inflammatory macrophages. Although several reports have demonstrated increased Wnt10b-β-catenin and VEGF expression after fractional laser irradiation in a mouse alopecia model, 37,38,44 we did not observe these differences in our single-cell RNA-seq analysis. Other reports have demonstrated that macrophages and the CCR2-TNFa signaling axis are involved in hair cycle progression, while dermal macrophages maintain hair follicle quiescence.…”
Section: Discussioncontrasting
confidence: 87%
“…Comprehensive single-cell gene expression analysis revealed that Ccr2 gene expression was elevated in recruited inflammatory macrophages. Although several reports have demonstrated increased Wnt10b-β-catenin and VEGF expression after fractional laser irradiation in a mouse alopecia model, 37,38,44 we did not observe these differences in our single-cell RNA-seq analysis. Other reports have demonstrated that macrophages and the CCR2-TNFa signaling axis are involved in hair cycle progression, while dermal macrophages maintain hair follicle quiescence.…”
Section: Discussioncontrasting
confidence: 87%
“…Our findings indicate that Wnt10b plays an important role during the SHF cycle of Angora rabbits. It was reported that Wnt10b can promote HF regeneration via inducing their switch from telogen to anagen (Zhang, Liu, et al., 2017). Hence, we infer that Wnt10b is a critical activator in cyclic transition of hair.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Wnt10b could promote HF development and regeneration by activating the canonical Wnt/β‐catenin signalling pathway (Li et al., 2013; Ouji et al., 2006). This may be achieved by inducing the switch from telogen phase to anagen phase (Zhang, Liu, et al., 2017). However, few studies of Wnt10b in rabbit HF cycling have been conducted (Li et al., 2013; Tosti et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies show increased human hair growth with valproic acid and, another Wnt/β‐catenin activator, methyl vanillate . Low‐level laser therapy also has been shown to stimulate hair growth by activating Wnt/β‐catenin signalling . Thus, activation of the WNT/β‐catenin pathway appears a promising potential therapeutic target in AGA.…”
Section: Key Issues In Hair Loss: From Physiology To Treatmentmentioning
confidence: 99%